Frequency of Attendance at Religious Services and Exposure to Environmental Tobacco Smoke - Gillum, Richard Frank (Journal of religion and health, 2021)
Exposure to environmental tobacco smoke (ETS) is associated with increased risk of disease and death. Reports on ETS and religion are lacking. Data from the National Health and Nutrition Examination Survey were used to test this association. In 4,712 nonsmokers, serum cotinine level of 0.05–3.99 ng/mL indicated ETS exposure. Frequency of attendance at religious services was categorized as > = weekly or less. In bivariate analysis, ETS exposure occurred in 28.6% of those with > = weekly attendance but 36.4% of less frequent attenders (p = 0.0004). In logistic regression controlling for multiple confounders OR = 0.72, 95%CI 0.61–0.85. ETS exposure was negatively associated with religion.